2009
DOI: 10.1016/j.bone.2009.03.668
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY in adolescent athletes with amenorrhea, eumenorrheic athletes and non-athletic controls

Abstract: Background Bone mineral density (BMD) is lower in amenorrheic athletes (AA) compared with eumenorrheic athletes (EA). Decreased energy availability and altered levels of appetite regulating hormones (ghrelin and leptin) in AA contribute to hypogonadism, an important cause of low BMD. The role of other nutritionally regulated hormones such as peptide YY (PYY) and adiponectin in mediating gonadal status and bone metabolism remains to be determined. Objectives Our objective was to determine whether PYY and adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 46 publications
7
47
2
3
Order By: Relevance
“…These results demonstrate that baseline adiponectin and ghrelin may not have a direct role in the development of BMD variables in prepubertal girls. In accordance with our results, previous studies have also found no relationship between adiponectin [4,16] and ghrelin [4,18] with BMD variables in physically active prepubertal children. Although some studies have reported significant correlations of BMD variables with adiponectin [11,12] and ghrelin [17,36], the results of current study suggest that during prepubertal development, adiponectin and ghrelin are not independent predictors of increases in BMD levels in contrast to FM and FFM values in prepubertal girls with different physical activity patterns.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results demonstrate that baseline adiponectin and ghrelin may not have a direct role in the development of BMD variables in prepubertal girls. In accordance with our results, previous studies have also found no relationship between adiponectin [4,16] and ghrelin [4,18] with BMD variables in physically active prepubertal children. Although some studies have reported significant correlations of BMD variables with adiponectin [11,12] and ghrelin [17,36], the results of current study suggest that during prepubertal development, adiponectin and ghrelin are not independent predictors of increases in BMD levels in contrast to FM and FFM values in prepubertal girls with different physical activity patterns.…”
Section: Discussionsupporting
confidence: 82%
“…Leptin concentrations have been related to FM and BMD values in healthy lean prepubertal girls [2,9], while the impact of lowered leptin concentrations on bone mass acquisition in the presence of elevated energy expenditure and reduced FM remains questionable in prepubertal and pubertal female RG [4,5,7,14,15]. Adiponectin has been related to BMD values in healthy untrained adolescent girls [11,12], while adiponectin did not predict BMD among prepubertal [4] and adolescent [16] female athletes. Similarly, circulating ghrelin has been reported to influence bone mineralization in untrained prepubertal [4] and adolescent [17] girls.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there is evidence that adiponectin increases with reduced energy [89,91] ; however, findings in amenorrheic athletes are inconsistent. There were no significant differences in adiponectin levels in adolescent amenorrheic versus eumenorrheic athletes [97] , but in another study, adult amenorrheic athletes were found to have higher adiponectin levels than eumenorrheic athletes [98] . Additionally, fat mass plays an important role in the regulation of ghrelin, cortisol, IGF-1, and peptide YY, which in turn affect GnRH regulation [ 74, 92-94 ; see also this vol., pp.…”
Section: Female Athlete Triadmentioning
confidence: 97%
“…Uno de los aspectos que parece influir negativamente en el remodelado óseo de las atletas adolescentes es la amenorrea (32,57). Por lo que podría ser interesante detectar a las atletas amenorreicas, ya que según estos estudios podrían presentar un remodelado óseo menor al correspondiente para su edad.…”
Section: Discussionunclassified